A Network Perspective on Dropout Prevention in Two Cities. (February 2015) - Wells, Rebecca; Gifford, Elizabeth; Bai, Yu; Corra, Ashley
Purpose: This exploratory case study examines how school systems and other local organizations have been working within two major U.S. cities to improve high school graduation rates. Systematically assessing active interorganizational dropout prevention networks may reveal characteristics affecting communities' capacity to support school completion.Research Method: This study included the local affiliates within two U.S. cities of national partners in a dropout prevention initiative. A survey and follow-up interview probed for each organization's cooperation with the other local organizations. Social network analyses revealed how school superintendents' offices and other local agencies cooperated, as well as which organizations were most central within each city's dropout prevention network.Findings: School systems in both cities cooperated with the YMCA, Big Brothers Big Sisters, Boys and Girls Club, the mayor's office, United Way, and Chamber of Commerce. Among the most central organizations in broader dropout prevention-related networks were the YMCA, Communities in Schools, mayor's office, and the United Way.Implications for Research and Practice: An organizational network perspective can help school systems identify strategic opportunities to build local capacity for supporting youth. Working with key brokers may then offer a feasible way for schools to leverage local resources.